Ghana, World, and Future: Translocality and National Development for Pan-Africanism, 1957-1968 - Emiljanowicz, Paul (My University, 2020)
As former colonies and newly independent states of the ‘Third World’ organized internationally around anticolonialism in the 1950s and 1960s, Ghana became a key site in debates over development at the height of the Cold War. Contributing to the new economic and political history of postcolonial Ghana, this study examines the national development visions and international political-economic connections of the Nkrumaist state 1957-66 and the first year under the post-coup National Liberation Council through the lens of translocality. Translocality refers to the entanglement of different localities and communities, and in this context, how the idea and practice of national development is co-constituted with these connections. Kwame Nkrumah situated national development as a resource in uniting the African continent against foreign political and economic influence. The Nkrumaist state played a leading role in the formation of the Organization of African Unity, non-alignment, nuclear non-proliferation, and attempts at harmonizing national development continentally. The movements of individuals to Ghana seeking participation within the Nkrumaist project were also racialized and gendered. Women Pan-Africanist activists organized conferences and made internationalist commentaries, making claims for inclusive economic development and participation. Furthermore, Ghanaian national development, dependent on mixed-planning foreign capital, markets, and technologies to finance projects, became increasingly subject to non-national departmental debates and an emerging liberal disciplinary politics through 1962-1966. The International Monetary Fund, Britain and the United States came to a consensus regarding a balance of payments and foreign reserve crisis in Ghana. After a military coup d'état in 1966, the NLC introduced an IMF reform package and embarked on a program of unmaking Nkrumaism. This study contributes to understanding the translocal dynamics of postcolonial development and development discourses.
Keywords: Ghana; Pan-Africanism; Translocality; Development; Global Political Economy; Decolonization